Arrangements Concerning Reclamation and Their Legal Impacts in View from UNCLOS 1982 - Tuhulele, Popi; Waas, Richard Marsilio; Makatita, Afrizal Anshari (SASI, 2023)
Introduction: Continuous development in a country automatically makes the country lack vacant land, and reclamation is one way to overcome this problem. Reclamation in its implementation has not been regulated in detail in the 1982 UNLCOS so it can cause problems in the future, such as what happened in the South China Sea where China carried out reclamation in the Spratly archipelago.Purposes of the Research: To find out and analyze reclamation arrangements in the 1982 UNCLOS and the impact of reclamation laws carried out by countries in terms of the 1982 UNCLOS.Methods of the Research: This study uses a normative juridical research type. By using the statutory approach, case approach, and conceptual approach. Management and analysis of legal material in this study use qualitative analysis.Results of the Research: The results showed that the 1982 UNCLOS did not regulate coastal reclamation, but there were several articles in the 1982 UNCLOS that related to coastal reclamation and could be used as a basis, namely Article 11, Article 12, Article 56, and Article 60. The impact of reclamation for the delimitation of sea areas between countries is that the state will take its own way of understanding and interpreting the contents of the convention for its own benefit, one of which is to carry out reclamation which can lead to delimitation disputes, especially in areas where an agreement on territorial boundaries has not been established as happened in reclamation disputes in the Spratly Islands. in the South China Sea by China.